PENGARUH KOMUNIKASI PEMASARAN DAN KELUHAN PELANGGAN TERHADAP REPUTASI BIZNET DI BALI - Subiakta, Krishna Wasudewa; I Dewa Ayu Hendrawathy Putri; I Wayan Wirta (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2024)
This study investigates the impact of marketing communication and customer complaints on Biznet's reputation in Bali, incorporating media convergence, network communication theory, and information processing theory. Data were gathered from Biznet customers in Bali through validated questionnaires and analyzed using quantitative methods, alongside multiple linear regression analysis techniques. The findings reveal that marketing communication positively and significantly influences Biznet's reputation in Bali, highlighting the necessity for Biznet to focus on effective marketing communication strategies to bolster its market reputation. Conversely, customer complaints have a significant impact on Biznet's reputation, suggesting the need for Biznet to efficiently address customer complaints to prevent reputational damage. Moreover, the combined effect of marketing communication and customer complaints on Biznet's reputation is significant, underscoring the importance of integrating effective marketing communication strategies with responsive customer complaint handling to cultivate a strong and positive reputation.